Short-term clinical and immunologic effects of scaling and root planing with Er : YAG laser in chronic periodontitis - Lopes, Beatriz M. V. [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP]; Thompson, Gloria M. A. [UNESP]; Neves, Lucia H. M. [UNESP]; Theodoro, Letícia Helena [UNESP] (Amer Acad Periodontology, 2008)
Background: Recently, the erbium-doped:yttrium, aluminum, and garnet (Er:YAG) laser has been used for periodontal therapy. This study compared Er:YAG laser irradiation (100 mJ/pulse, 10 Hz, 12.9 J/cm(2)) with or without conventional scaling and root planing (SRP) to SRP only for the treatment of periodontal pockets affected with chronic periodontitis.Methods: Twenty-one subjects with pockets from 5 to 9 mm in non-adjacent sites were studied. In a split-mouth design, each site was randomly allocated to a treatment group: SRP and laser (SRPL), laser only (L), SRP only (SRP), or no treatment (C). The plaque index (PI), gingival index (GI), bleeding on probing (BOP), and interleukin (IL)-1 beta levels in crevicular fluid were evaluated at baseline and at 12 and 30 days postoperatively, whereas probing depth (PD), gingival recession (GR), and clinical attachment level (CAL) were evaluated at baseline and 30 days after treatment. A statistical analysis was conducted (P<0.05).Results: Twelve days postoperatively, the PI decreased for SRPL and SRP groups (P<0.05); the GI increased for L, SRP, and C groups but decreased for the SRPL group (P<0.05); and BOP decreased for SRPL, L, and SRP groups (P<0.01). Thirty days postoperatively, BOP decreased for treated groups and was lower than the C group (P<0.05). PD decreased in treated groups (P<0.001), and differences were found between SRPL and C groups (P<0.05). CAL gain was significant only for the SRP group (P<0.01). GR increased for SRPL and L groups (P<0.05). No difference in IL-1 beta was detected among groups and periods.Conclusion: Er:YAG laser irradiation may be used as an adjunctive aid for the treatment of periodontal pockets, although a significant CAL gain was observed with SRP alone and not with laser treatment.
Keywords: clinical trial; cytokine; dental scaling; lasers; Er : YAG; periodontitis; root planing